For Onomatopoeia in the Model-Experiments - SODA, Toyoji; FUKUYO, Kazumasa; MORI, Toshifumi; OHTA, Michiru (OTOLOGIA FUKUOKA, 1984)
Tinnitus, an abnormality of auditory sensation, is a frequently encountered complaint in daily clinical work. The patients of tinnitus in Japan are usually trying to complain it by expressing with using onomatopoeia. Onomatopoeia are characteristic to Japanese language and are not observed in the other languages. We present the preliminary experiments which were performed as a model in order to examine the background of these onomatopoeia. Normal subjects can explain pure tones and narrow band noises linguistically using onomatopoeia in the model-experiments. In results, typical onomatopoeia expressed boo-n, poo-n are equivalent to low ranged pure tones, pee-n, kee-n, shee-n are to high range of pure tones as well. In the same manner, go-n, za- for low tone range of narrow band noises and shu-, shee-n are similar to high tone of narrow band noises. The characteristics of explanations on onomatopoeia were very different in those of vowels in the onomatopoeia.